Disclosure policy: A discussion of Leuz, Triantis and Wang (2008) on “going dark” - Coles, Jeffrey L. (Journal of Accounting and Economics, 2008)
LTW (2008) examine firms withdrawing from the SEC reporting system but continuing to trade on Pink Sheets. The paper finds that Sarbanes-Oxley increased the propensity of firms to go dark but, counter to conventional wisdom, had no significant effect on the rate of going-private transactions. Agency costs, as well as poor growth opportunities, proximity to financial distress, and increased compliance costs arising from SOX increase the propensity to go dark. Suggestions to improve the empirical implementation and interpretation involve including additional control and more suitable explanatory variables, and more attention to causation issues and to the quantification of economic significance.